Environmental problems of intensive technologies of cultivation of crops - Ivaschenko, A.A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Тo disclose the adverse environmental effects of application of intensive technologies of cultivation of agricultural crops and the need to develop alternative ways of improvement through simulation of natural processes, the application of biological methods of protection from pests and development of ecological techniques of application of pesticides on target objects — plants.